Diversity of bird species in Pangheotan grassland and Mount Masigit Kareumbi Hunting Park, West Java, Indonesia - SUSANTI WITHANINGSIH; PARIKESIT PARIKESIT; RAKHA RAKHA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Withaningsih S, Parikesit, Rakha. 2022. Diversity of bird species in Pangheotan grassland and Mount Masigit Kareumbi Hunting Park, West Java, Indonesia. Biodiversitas 23: 2790-2798. The diversity of bird species is often used as an indicator of the ecosystem balance of an area. One of the efforts to preserve and protect the diversity of bird species is made by fostering habitat in the Pangheotan I Grassland (Kebun Rumput Pangheotan, hereinafter Pangheotan grassland) of PT. Perkebunan Nusantara (PTPN) VIII, West Bandung District, Indonesia and the Wali Pohon Block of Mount Masigit Kareumbi Hunting Park (Taman Buru Gunung Masigit Kareumbi herein after TBGMK), Bandung District, Indonesia. This study aims to determine the diversity of bird species in the two areas so that it can be used as basic data in making planning strategies for maintaining and increasing biodiversity. Bird data collection techniques using the point count method and analysis of bird species diversity data were carried out using a quantitative data analysis approach. In the second year of habitat development, 27 species of birds were found in Pangheotan grassland, with a Shannon-Wiener diversity index (H') of 2,479 (medium diversity), an evenness index of 0.814 (even abundance), and Pycnonotus aurigaster was the species of bird that had the highest relative frequency and relative abundance. Meanwhile, in the second year of habitat development in TBGMK, 45 species of birds were found with H' of 3,237 (high diversity), and E of 0.926 (even abundance), and srigunting kelabu (Dicrurus leucophaeus) was the species of bird that had the highest relative frequency and relative abundance. The results of the study show the success of the habitat development carried out in these two locations through the biodiversity by design program.